Green-Building-Index-Assessment-Criteria-Based Comparative Evaluation of Interlocking Blocks as an Alternative to Conventional Masonry for Residential Buildings in Malaysia - Mohd, S.S.R. (IOP Publishing Ltd, 2021)
Major residential construction projects adopt clay bricks as masonry, which can contribute to high carbon emission, primarily due to their high embodied carbon. Furthermore, the adoption of conventional masonry, including clay bricks, may lead to the use of high amounts of mortar and contribute to a lot of wastage. Therefore, an alternative system that can potentially replace conventional masonry is required to reduce the wastage as well as carbon emission. Interlocking blocks, which adopt a lock and key system has the potential to replace conventional masonry as they employ locally available materials, save construction time, use less mortar and are less dependent on highly skilled masons. In view of their potential, the adoption of interlocking blocks in residential buildings were evaluated comparatively to conventional masonry, namely clay and cement sand bricks, based on the Green Building Index Assessment Criteria for Residential New Construction (GBI-RNC) tool. Overall Thermal Transfer Values of test models that employed conventional masonry and interlocking blocks were calculated. Approximately, based on the GBI-RNC tool, with an increase of 17-18 points achieved from the EE, MR and IN criteria, a Silver rating can be achieved with the adoption of interlocking blocks. Â© Published under licence by IOP Publishing Ltd.